EFEKTIVITAS TEKNIK SELF MANAGEMENT UNTUK MENINGKATKAN KEDISIPLINAN PESERTA DIDIK KELAS VII DI SMP ISLAM IBNU KHALDUN BANDA ACEH - Wanty Khaira (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2021)
Discipline is a student's behavior that is formed through the process of a set of habits that show the values of obedience, obedience, order and order based on norm values. Students who have discipline will show obedience and regularity to their role as a student, namely students in a directed and orderly manner. This research was conducted at Ibnu Khaldun Islamic Middle School in Banda Aceh against the background of the problem of lack of students in managing time, because Ibnu Khaldun Islamic Middle School is a boarding school (dayah), therefore almost all students experience personal problems, especially on discipline. This study aims to determine self-management techniques before and after effective group guidance services are provided to improve student discipline in Ibnu Khaldun Islamic Middle School Banda Aceh. Researchers use quantitative methods and use the type of pre-experimental research (pre-experimental) with One Group Pre-test and Post-test Design. Data collection used is a Likert scale. Analysis techniques using the normality test and t-test. The population in this study were grade VII students of Ibnu Khaldun Islamic Middle School in Banda Aceh. There are 61 students with high, medium and low discipline, while the sample is 7 students representing class VII. The sample is chosen through purposive sampling with the categorization of students with the lowest level of discipline. From the results of this study it can be concluded that, the results of the study show effective self management techniques to improve the discipline of students in grade VII in Ibnu Khaldun Islamic Middle School Banda Aceh.